Fetal Presentation Abnormality in a Dunkin Hartley Guinea Pig (Cavia porcellus) - P. Jalantha; M. Thangapandiyan; Cecilia Joseph; M.R. Srinivasan; C. Soundararajan (The Indian Veterinary Journal, 2024)
Dystocia is difficult for parturition due to maternal or foetal causes that requires assistance for delivery. The expected incidence rate of dystocia is more in laboratory animals. A rare case report of dystocia in a guinea pig (Cavia porcellus) due to foetal cause is presented. A one-and-a-half-year-old healthy full term pregnant female guinea pig was found dead in her cage and was subjected to post-mortem examination to identify the cause of death. In the right uterine horn, the caudal foetus weighing 124 g was in breech presentation with right unilateral hock flexion and the cephalad foetus of weight 119g was in the anterior presentation. The larger size of the foetuses with various foetal presentation and postural abnormalities have attributed to dystocia and death of the sow in this present case.